An Integrated Deep Learning-Based Data Fusion and Degradation Modeling Method for Improving Prognostics - Wang, Di; Liu, Kaibo (IEEE transactions on automation science and engineering, 2024)
Accurate prognostics are crucially important to prevent unexpected failures in industrial and service systems. This process aims to monitor the degradation status of units and predict their remaining useful lifetime (RUL) by analyzing the data collected from multiple sensors. Existing studies for prognostics either focus on health index (HI)-based statistical fusion methods that are limited by restrictive assumptions or machine learning methods that model the HI and degradation status in two separate steps. However, the restrictive assumptions are often invalid in practice, and the intrinsic connection between the HI and degradation status is missing if the two parts are modeled separately, leading to poor prognostic results. This paper proposes an integrated deep learning-based data fusion and degradation modeling method by integrating a deep neural network (DNN) and a long short-term memory (LSTM) to characterize the nonlinear relationship between the HI and multiple sensor signals and to describe the underlying degradation status of units. In particular, our innovative idea is to develop an integrated backpropagation parameter estimation algorithm to solve the fusion procedure and the degradation modeling in an integrated manner by considering the properties of HI construction in the loss functions. Thus, the constructed HI is expected to better characterize the underlying degradation process and lead to a superior prognostic result. In the case study on the degradation of aircraft gas turbine engines, the proposed method achieves promising performance compared with the existing benchmarks of statistical models and other deep learning models. Note to Practitioners-This paper develops an integrated deep learning-based data fusion and degradation modeling method for improving prognostics when multiple sensors are available to monitor the degradation status of a unit. There are four steps for implementing this method in practice: 1) collecting multiple sensor signals of historical units; 2) constructing the HI and modeling the degradation status of units by combining a DNN model and an LSTM model; 3) solving the fusion procedure and the degradation modeling in an integrated manner by developing an integrated backpropagation parameter estimation algorithm; and 4) making prognostics for in-service units. The novelty of the proposed method is that it conducts prognostics by combining a DNN fusion model and an LSTM degradation model, and seamlessly integrates the fusion procedure with the degradation modeling to construct the HI for better characterizing the status of a unit. As a result, the proposed method has two main advantages: (i) capable of characterizing various degradation processes of different engineering systems; and (ii) superior prognostic results by constructing more suitable HI for the degradation process.